Trends and Challenges in Robotic Applications - Gracia, Luis; Perez-Vidal, Carlos (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Research performed on robotic applications has significantly expanded in the last decade, and currently, robotic systems are being utilized for many purposes. To achieve this generalized application of robots, researchers have endeavoured to study a wide variety of methods and algorithms in order to properly employ robotic systems in many real-life scenarios. At present, many types of robotic platforms are being employed in various applications, e.g., dual-arm robots, parallel robots, mobile robots, humanoid robots, aerial robots, underwater robots, and micro/nano robots. Moreover, some theoretical tools are specially being used to obtain correct robot performance, e.g., machine learning, artificial intelligence, multi-agent systems, and control and planning theory. The purpose of this reprint is to exhibit the current state of robotic applications. In particular, in addition to introducing novel theories and methods, this reprint is particularly focused on the application of robotic systems in real-life situations. Thus, the presentation of experimental results makes evident the feasibility and usefulness of robotic systems in practical cases. Obviously, this reprint does not intend to exhaustively demonstrate all the current existing robotic applications but rather give an overview of them, revealing the high level of activity in this area. This reprint contains an Editorial, together with 30 contributions in total from countries all around the world, addressing a broad range of robotic applications.